Targeting EphA2 in Bladder Cancer Using a Novel Antibody-Directed Nanotherapeutic - Walid Kamoun; Elden Swindell; Christine Pien; Lia Luus; Jason Cain; Minh Pham; Irawati Kandela; Zhaohua Richard Huang; Suresh K. Tipparaju; Alexander Koshkaryev; Vasileios Askoxylakis; Dmitri B. Kirpotin; et al. (MDPI AG, 2020)
Ephrin receptor A2 (EphA2) is a member of the Ephrin/Eph receptor cell-to-cell signaling family of molecules, and it plays a key role in cell proliferation, differentiation, and migration. EphA2 is overexpressed in a broad range of cancers, and its expression is in many cases associated with poor prognosis. We recently developed a novel EphA2-targeting antibody-directed nanotherapeutic encapsulating a labile prodrug of docetaxel (EphA2-ILs-DTXp) for the treatment of EphA2-expressing malignancies. Here, we characterized the expression of EphA2 in bladder cancer using immunohistochemistry in 177 human bladder cancer samples and determined the preclinical efficacy of EphA2-ILs-DTXp in four EphA2-positive patient-derived xenograft (PDX) models of the disease, either as a monotherapy, or in combination with gemcitabine. EphA2 expression was detected in 80-100% of bladder cancer samples and correlated with shorter patient survival. EphA2 was found to be expressed in tumor cells and/or tumor-associated blood vessels in both primary and metastatic lesions with a concordance rate of approximately 90%. The EphA2-targeted antibody-directed nanotherapeutic EphA2-ILs-DTXp controlled tumor growth, mediated greater regression, and was more active than free docetaxel at equitoxic dosing in all four EphA2-positive bladder cancer PDX models. Combination of EphA2-ILs-DTXp and gemcitabine in one PDX model led to improved tumor growth control compared to monotherapies or the combination of free docetaxel and gemcitabine. These data demonstrating the prevalence of EphA2 in bladder cancers and efficacy of EphA2-ILs-DTXp in PDX models support the clinical exploration of EphA2 targeting in bladder cancer.